Information method for control of green glass production - R. I. Makarov; E. R. Khorosheva (Тонкие химические технологии, 2021)
Objectives. The technological process for the production of sheet glass by the float method is continuous and large-scale. Most European cars (up to 90%) are factory-tinted green; the bulk of the glass is painted in the desired color during the production process. The introduction of modern information technologies and digitalization has opened up opportunities for a significant increase in the efficiency of glass production. Accounting for the amount of drawn and cut glass allows you to evaluate an important indicator of the production work—the glass utilization rate, which determines the percentage of quality glass in the total output. The yield of the quality glass depends on the technological waste in the production process. To assess the effect of waste arising at the production stages on the glass utilization rate, an analysis of the statistical data of the float line operation was carried out. These statistical data differ from the normal law of probability distribution, which limits the use of traditional statistical control methods. Regression models do not always give an accurate mathematical description of the process since the variance of the conditional mathematical expectation of the output variable relative to the input is not a consistent characteristic of the relationship between the input and output variables. The purpose of this work is to study the application of information modeling theory for the analysis and control of the technological process of green glass production in terms of its utilization rate.Methods. The technique of modeling technological chains has some peculiarities with that for operations modeling. It analyzes operations to identify possible information links between parameters. Thus, the process of obtaining the utilization rate of green glass in the production process can be followed. This study analyzes the influence of the paired and triple interactions of waste on the process of affording the utilization rate of glass at the stages of green glass production.Results. Information modeling of the technological process of affording the utilization rate of green glass in the production process has been carried out. Informational analysis results in a conclusion about the sufficiency of the control of the utilization rate of green glass in the production process according to informatively related parameters—waste at the stages of glass melting, annealing, and flanging.Conclusions. The selected method of information control of the glass utilization rate can be used in quality management systems in the production of green glass by the float method.